Carbon monoxide (CO) cycling in the Fram Strait, Arctic Ocean - Campen, Hanna I.; Arévalo-Martínez, Damian L.; Bange, Hermann W. (Biogeosciences, 2023)
Carbon monoxide (CO) influences the radiative budget and oxidative capacity of the atmosphere over the Arctic Ocean, which is a source of atmospheric CO. Yet, oceanic CO cycling is understudied in this area, particularly in light of the ongoing rapid environmental changes. We present results from incubation experiments conducted in the Fram Strait in August–September 2019 under different environmental conditions: while lower pH did not affect CO production (GPCO) or consumption (kCO) rates, enhanced GPCO and kCO were positively correlated with coloured dissolved organic matter (CDOM) and dissolved nitrate concentrations, respectively, suggesting microbial CO uptake under oligotrophic conditions to be a driving factor for variability in CO surface concentrations. Both production and consumption of CO will likely increase in the future, but it is unknown which process will dominate. Our results will help to improve models predicting future CO concentrations and emissions and their effects on the radiative budget and the oxidative capacity of the Arctic atmosphere.